Incorporated Fish Oil Fatty Acids Prevent Action Potential Shortening Induced by Circulating Fish Oil Fatty Acids - Den Ruijter, Hester M.; Verkerk, Arie O.; Coronel, Ruben (Frontiers in Physiology, 2010)
Increased consumption of fatty fish, rich in omega-3-polyunsaturated fatty acids (ω3-PUFAs) reduces the severity and number of arrhythmias. Long-term ω3-PUFA-intake modulates the activity of several cardiac ion channels leading to cardiac action potential shortening. Circulating ω3-PUFAs in the bloodstream and incorporated ω3-PUFAs in the cardiac membrane have a different mechanism to shorten the action potential. It is, however, unknown whether circulating ω3-PUFAs in the bloodstream enhance or diminish the effects of incorporated ω3-PUFAs. In the present study, we address this issue. Rabbits were fed a diet rich in fish oil (ω3) or sunflower oil (ω9, as control) for 3 weeks. Ventricular myocytes were isolated by enzymatic dissociation and action potentials were measured using the perforated patch-clamp technique in the absence and presence of acutely administered ω3-PUFAs. Plasma of ω3 fed rabbits contained more free eicosapentaenoic acid (EPA) and isolated myocytes of ω3 fed rabbits contained higher amounts of both EPA and docosahexaenoic acid (DHA) in their sarcolemma compared to control. In the absence of acutely administered fatty acids, ω3 myocytes had a shorter action potential with a more negative plateau than ω9 myocytes. In the ω9 myocytes, but not in the ω3 myocytes, acute administration of a mixture of EPA + DHA shortened the action potential significantly. From these data we conclude that incorporated ω3-PUFAs into the sarcolemma and acutely administered ω3 fatty acids do not have a cumulative effect on action potential duration and morphology. As a consequence, patients with a high cardiac ω3-PUFA status will probably not benefit from short term ω3 supplementation as an antiarrhythmic therapy.